Carboplatin-loaded SMNDs to reduce GSH-mediated platinum resistance for prostate cancer therapy. Issue 43 (17th October 2018) - Liang, Shuang; Han, Leiqiang; Mu, Weiwei; Jiang, Dandan; Hou, Teng; Yin, Xiaolan; Pang, Xiuping; Yang, Rui; Liu, Yongjun; Zhang, Na
Abstract : Glutathione (GSH)-mediated drug resistance can strongly weaken the therapeutic efficiency of platinum(ii ). Abstract : Glutathione (GSH)-mediated drug resistance can strongly weaken the therapeutic efficiency of platinum(ii ). Therapeutic platforms developed based on small-molecule-based nanodrugs (SMNDs) have gained great attention due to their unique properties. Herein, a novel SMND of carboplatin–lauric acid nanoparticles (CBP–LA NPs) was developed for the first time to reduce GSH-mediated platinum resistance and improve the antitumor efficiency of platinum(ii ). A CBP–LA conjugate was synthesized and CBP–LA NPs were prepared. Intracellular glutathione determination and intracellular Pt–DNA adduct assay were performed. Then the cellular cytotoxicity, cellular uptake, targeted biodistribution and in vivo antitumor efficacy of CBP–LA NPs were investigated. The CBP–LA conjugate could self-assemble into nanoparticles with small, uniform size and high drug loading (48%). The CBP–LA NPs exhibited a low critical aggregation concentration of 1.4 μg mL −1 and outstanding plasma stability in vitro . Under reduced conditions, the CBP–LA NPs showed redox-responsive behavior. The intracellular glutathione determination and the Pt–DNA adduct assay revealed that CBP–LA NPs could reduce the intracellular GSH levels and improve the efficiency of platinum chelating with DNA, which would overcome GSH-mediated platinum(ii ) resistance. The cellular uptake study revealed that CBP–LA NPs were internalized by tumor cells, which was very beneficial for improving the therapeutic efficiency. Furthermore, an in vivo study demonstrated that CBP–LA NPs significantly enhanced drug accumulation at tumor sites and improved antitumor efficiency ( p < 0.05) compared to the CBP solution group. This study suggests that CBP–LA NPs are a potential formulation to enhance prostate cancer therapy.